A formation of conceptual framework to enhance innovative behaviors of Kuwait Public sector employees. - Almerri, Khalifah (Human Resource Management Academic Research Society (HRMARS), 2023)
Human capital and social capital have emerged as major concerns in the new global economy as significant resources for the countries. Additionally, intellectual capital is crucial for achieving economic success in the field of sustained competitive advantage. A useful business resource may also contribute to a company's success. According to a firm's use of distinctive resources will give it a competitive advantage, which is essential for commercial success. Along with good and practical business resources, creativity on the part of both employers and employees also plays a role in the growth and administration of businesses. In order to lay the foundation for the current survey, this study discusses two of the hypotheses that have been proposed by other studies addressing corporate resources. The research framework was developed using multiple theories such as self-determination theory, Resource Dependence Theory, and Resources-based View (RBV). This study presents a conceptual framework to examine how intellectual capital (human, relational, structural), enhances innovation in developing countries’ education sector, furthermore study proposed that job autonomy and collaborative culture can moderate the relationship between intellectual capital towards innovation.